Forms of business organization and rural enterprise development: Some examples from Anglophone Africa - Zesch, Scott K. (World development, 1989)
For rural enterprises in transition from the informal to the formal sector, the legal form of business organization adopted can significantly affect the management of the firm. Partnerships are simple and flexible but may be too loosely structured for some commercial ventures. Cooperative societies are more formally structured than partnerships and are subject to less complicated statutory requirements than companies, although they are vulnerable to far- reaching government intervention. Companies are generally more attractive to institutional lenders and passive investors; however, their complexity makes them better suited to entrepreneurs with substantial business experience.